Mass calibration of the CODEX cluster sample using SPIDERS spectroscopy – II. The X-ray luminosity–mass relation. Issue 2 (14th April 2020) - Capasso, R; Mohr, J J; Saro, A; Biviano, A; Clerc, N; Finoguenov, A; Klein, M; Grandis, S; Collins, C; Damsted, S; Kirkpatrick, C; Kukkola, A
ABSTRACT: We perform the calibration of the X-ray luminosity–mass scaling relation on a sample of 344 CODEX clusters with z < 0.66 using the dynamics of their member galaxies. Spectroscopic follow-up measurements have been obtained from the SPIDERS survey, leading to a sample of 6658 red member galaxies. We use the Jeans equation to calculate halo masses, assuming an NFW mass profile and analysing a broad range of anisotropy profiles. With a scaling relation of the form L_X A_XM_200c^B_X E(z)^2 (1+z)^γ _X, we find best-fitting parameters A_X=0.62^+0.05_-0.06 (± 0.06)× 10^44 erg s^-1, B_X=2.35^+0.21_-0.18(± 0.09), γ _X=-2.77^+1.06_-1.05(± 0.79), where we include systematic uncertainties in parentheses and for a pivot mass and redshift of 3× 10^14 M_ and 0.16, respectively. We compare our constraints with previous results, and we combine our sample with the SPT SZE-selected cluster subsample observed with XMM–Newton extending the validity of our results to a wider range of redshifts and cluster masses.